Formulation of Balanced Scorecard for Performance Assessment of Mosque Prosperity Council Organization - Purwani, Rika; Widana, Gusti Oka (AIBPM Publisher, 2023)
The Mosque Prosperity Council or Dewan Kemakmuran Masjid (DKM) has a role in managing Islamic funds which include zakat, infaq, sadaqah and waqf, the use of which is aimed at improving the welfare of the people. In order to be able to play its important role in achieving and increasing efficiency and effectiveness in the management of community funds, the Mosque Prosperity Council is expected to have a formulation for performance analysis and determining strategic steps in organizational development. Through a descriptive qualitative approach based on literature or literature review, researchers compiled a balanced scorecard formulation with 4 (four) assessment perspectives, namely financial perspective, learning and growth perspective, internal business process perspective, and customer perspective as an analytical tool for measuring the performance of the Mosque Prosperity Council. By identifying these four perspectives, it is then expected to be able to interpret the condition and performance of the Mosque, so that it can help the Mosque in identifying areas of strength and areas of improvement, as well as formulating strategic goals for the development of its organization. It can also help the Mosque to communicate its progress and impact to stakeholders, including worshipers, donors, government and the wider community.